Keanekaragaman dan Potensial Musuh Alami Koloni Tetragonula leaviceps (Hymenoptera: Apidae: Meliponinae) - Hashifah, Fathimah Nurfithri; Indraswari Suhri, Andi Gita Maulidyah; Nafisah, Nur Apriatun; Wahyudi, Christosie Immanuel (Universitas Sarjanawiyata Tamansiswa, 2025)
This study discusses the diversity of natural enemies of Tetragonula leaviceps (stingless) bees. The natural enemies obtained act as predators, honey thieves, and nest destroyers (intruders). This research was conducted from September to November 2020 at Caping Merapi Plantation Sleman, Yogyakarta. This research uses the random sampling method in collecting species. All natural enemies that have been identified were obtained as many as 11 species of natural enemies of Tetragonula leaviceps bees. These species were identified from 628 individuals consisting of Insecta, Arachnida, and Reptilia classes. All classes are potential predators, but those that act as honey thieves and nest destroyers are only from the Formicidae family. The results of this study are expected to increase knowledge in stingless bee farming so that it can further maximise nest boxes, nest areas or habitats, and supporting plants as a source of bee food.